Use of specific ELISA for the detection of antibodies directed against p53 protein in patients with hepatocellular carcinoma. - Ryder, Stephen D.; Rizzi, P. M.; Volkmann, Martin; Metivier, E.; Pereira, L. M.; Galle, Peter R.; Naoumov, N. V.; Zentgraf, Hanswalter; Williams, R. (Journal of clinical pathology, 1996)
AIMS: To analyse the significance of antibodies to p53 protein as a serological marker for changes in p53 gene expression in patients with hepatocellular carcinoma. METHODS: Thirty eight patients with hepatocellular carcinoma, 19 showing accumulation of p53 protein by immunohistochemistry and 19 having no accumulation, were studied. The presence of anti-p53 was tested using a novel ELISA utilising a recombinant p53 protein as a capture system and verified by western blotting. p53 gene mutations were sought by single strand conformational polymorphism and DNA sequencing analyses. RESULTS: Of 19 patients with p53 protein accumulation in tumour tissue, 10 (52%) had antibodies to p53 in serum by ELISA. Four patients with p53 negative immunohistochemistry also had detectable anti-p53. Western blot analysis confirmed the specificity of the ELISA positive serum samples. The presence of anti-p53 was independent of serum alpha-fetoprotein and was detected in 50% of small tumours while only 8% were alpha-fetoprotein positive. Mutations affecting exons 5 and 6 seem to be more frequently associated with development of anti-p53, than mutations in exons 7 or 8. CONCLUSIONS: The ELISA for anti-p53 is a convenient and specific tet for the detection of humoral response to alterations in p53 gene expression and could be of value in the diagnosis and characterisation of patients with hepatocellular carcinoma.